(untitled) (Revista da Faculdade de Medicina Veterinária e Zootecnia da Universidade de São Paulo, 1975)
Seventy seven throughbred horses of São Paulo state, among them 52 attacked by toxoplasmosis and 25 normals, were grouped according to the observed signs: 1) with incoordination (24 animals); 2) females that suffered, in the past, at least one abortion (23 animals); 3) excessive irritability (5 animals); 4) without signs (25 animals). Blood samples of all animals were examined by the Sabin-Feldman test and all 52 sick animals were positive and the antibody titer varied from 64 to 4000 and more frequent value of the antibody level was 1000. Among the animals of the control group, 24 serum specimens were negative and one was positive at the 1:16 dilution. The results suggest that the infection by the Toxoplasma gondii was recently introduced in horse population.